2016
DOI: 10.4236/jss.2016.45008
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Economic Partnerships, Exchange Rate Policy and Agricultural Trade: A Gravity Model Analysis of China’s Agricultural Trade Flows

Abstract: Agricultural trade in China is greatly influenced by government policy activities particularly regional integration agreements, strategic economic partnerships and exchange rate policy. China's agricultural sector has grown significantly in the past two decades however the factors that have led to this growth have not been fully explored. This study applied the Gravity model in analyzing China's bilateral agricultural trade flows with its major agricultural trading partners namely USA,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There are greater business opportunities in China's agricultural export trade, but the difficulty of export is also increasing. Finally, according to the research results, it puts forward countermeasures and suggestions to improve the competitiveness and trade potential of China's agricultural exports to the BRICS countries [6][7][8] [9]. Qu Yi (2017), analyzed "Agricultural Trade Cost Research [10].…”
Section: Literature Review 21 China's Agricultural Product Tradementioning
confidence: 99%
“…There are greater business opportunities in China's agricultural export trade, but the difficulty of export is also increasing. Finally, according to the research results, it puts forward countermeasures and suggestions to improve the competitiveness and trade potential of China's agricultural exports to the BRICS countries [6][7][8] [9]. Qu Yi (2017), analyzed "Agricultural Trade Cost Research [10].…”
Section: Literature Review 21 China's Agricultural Product Tradementioning
confidence: 99%
“…There are the same basic findings in this model's different implementations: distances and boundaries are important determinants to describe the trade flow. For example, the researchers used the gravity model to determine Chinese agricultural foreign trade with its major partners (Muganyi & Chen, 2016). The researcher used the gravity model to examine the Trade Potential of Senegal and Morocco (Niang, 2016).…”
Section: Literature Review About Using the Gravity Modelmentioning
confidence: 99%
“…Evidence from a series of published papers has shown that gravity model can be derived from both Ricardian and HO models. Adding to that, Anderson (1979) as well specified that the gravity framework is consistent with a world trade model in which products are differentiated by the country of origin (Muganyi and Chen, 2016). Though research on gravity model theoretical bases is still underway, its predictive power in international trade analysis has proved to be important.…”
Section: The Gravity Model Historical Development and Its Specificationmentioning
confidence: 99%
“…It as well omits the impact of time invariant characteristics as aforesaid, this is essentially to precisely evaluate the net impact of predictor variables on the principle or outcome variable. The principal challenge of FEM is that time invariant variables cannot be estimated directly in this model (Muganyi and Chen, 2016). Hence variables such as culture and distance between countries will not be supported in the FEM.…”
Section: Estimation Proceduresmentioning
confidence: 99%